PERAN RELIGI DAN TRADISI SPIRITUAL DALAM PEMBENTUKAN IDENTITAS PSIKOLOGIS MASYARAKAT SASAK DI LOMBOK - Danang Nur Adiwibawa (Nusantara Hasana Journal, 2024)
This study aims to examine the role of religion and spiritual traditions in the formation of the psychological identity of the Sasak people in Lombok. The Sasak people, as a community rich in tradition, integrate Islamic values ​​with local wisdom, creating a unique collective identity. The method used is qualitative research with a phenomenological approach, involving in-depth interviews, participatory observation, and Focus Group Discussion (FGD) with informants consisting of traditional figures, religious leaders, and community members who are active in traditional practices. The results of the study indicate that religious practices such as pengajian, Rowah ceremonies, and Bau Nyale rituals function as a medium to instill the values ​​of solidarity, piety, and cultural pride. Although modernization challenges the sustainability of tradition, the Sasak people still maintain their identity through involvement in traditional activities. This study confirms that the psychological identity of the Sasak people is formed by a complex interaction between spiritual values ​​and cultural practices, as well as its important implications for cultural preservation and character education. The results of this study are expected to provide insight into the development of cultural preservation programs and strengthening community identity in the era of globalization.